Gold nanoparticles attenuate the interferon-γ induced SOCS1 expression and activation of NF-κB p65/50 activity via modulation of microRNA-155-5p in triple-negative breast cancer cells - Farhana, Aisha; Alsrhani, Abdullah; Rasheed, Naila; Rasheed, Zafar (Frontiers in Immunology, 2023)
Objective Triple-negative breast cancer (TNBC) is a very aggressive form of cancer that grows and spreads very fast and generally relapses. Therapeutic options of TNBC are limited and still need to be explored completely. Gold nanoparticles conjugated with citrate (citrate-AuNPs) are reported to have anticancer potential; however, their role in regulating microRNAs (miRNAs) in TNBC has never been investigated. This study investigated the potential of citrate-AuNPs against tumorigenic inflammation via modulation of miRNAs in TNBC cells. Methods Gold nanoparticles were chemically synthesized using the trisodium-citrate method and were characterized by UV-Vis spectrophotometry and dynamic light scattering studies. Targetscan bioinformatics was used to analyze miRNA target genes. Levels of miRNA and mRNA were quantified using TaqMan assays. The pairing of miRNA in 3'untranslated region (3'UTR) of mRNA was validated by luciferase reporter clone, containing the entire 3'UTR of mRNA, and findings were further re-validated via transfection with miRNA inhibitors. Results Newly synthesized citrate-AuNPs were highly stable, with a mean size was 28.3 nm. The data determined that hsa-miR155-5p is a direct regulator of SOCS1 (suppressor-of-cytokine-signaling) expression and citrate-AuNPs inhibits SOCS1 mRNA/protein expression via modulating hsa-miR155-5p expression. Transfection of TNBC MDA-MB-231 cells with anti-miR155-5p markedly increased SOCS1 expression (p<0.001), while citrate-AuNPs treatment significantly inhibited anti-miR155-5p transfection-induced SOCS1 expression (p<0.05). These findings were validated by IFN-γ-stimulated MDA-MB-231 cells. Moreover, the data also determined that citrate-AuNPs also inhibit IFN-γ-induced NF-κB p65/p50 activation in MDA-MB-231 cells transfected with anti-hsa-miR155-5p. Conclusion Newly generated citrate-AuNPs were stable and non-toxic to TNBC cells. Citrate-AuNPs inhibit IFN-γ-induced SOCS1 mRNA/protein expression and deactivate NF-κB p65/50 activity via negative regulation of hsa-miR155-5p. These novel pharmacological actions of citrate-AuNPs on IFN-γ-stimulated TNBC cells provide insights that AuNPs inhibit IFN-γ induced inflammation in TNBC cells by modulating the expression of microRNAs.